National survey of occupational advice for lower limb arthroplasty patients. (3rd February 2020) - Tsang, B; McDonald, D; McNamara, I; Kottam, L; Rangan, A; Baker, P
Abstract: Background: Little is known what advice or support patients are given about return to work (RTW) after hip or knee replacement surgery. Aims: This study aims to understand the delivery, timing and content of 'RTW' advice currently delivered by surgical teams offering hip and knee replacements across the UK. Methods: National online survey exploring five specific areas relating to 'RTW' advice: (i) timings of interactions between hospital orthopaedic teams and patients prior to surgery, (ii) routine delivery of 'RTW' advice, (iii) methods used to deliver 'RTW' advice, (iv) confidence delivering advice and (v) need for an occupational 'RTW' advice intervention. Results: A total of 152 participants including surgeons, physiotherapists, occupational therapists and nurses from 59 different public and private health providers responded. Only 20% ( n = 30) of respondents reported that working patients were identified as a specific subgroup in need of additional support. Overall, 62% ( n = 92) stated that they did not routinely offer 'RTW' advice. When given, 'RTW' advice was almost always verbal, generic advice using blanket timescales and based on the respondent's anecdotal experience rather than the patients individualized needs. Overall, 116 (78%) felt an occupational advice intervention was needed. Conclusions: This national survey demonstrated wide variation in the timing, content and delivery of information and advice for patients in work and intending to RTW after hip and knee replacement surgery. Current RTW advice provided to hip and knee replacement patients is inadequate.